THE CREATIVE WORK OF BORIS VIAN WITHIN FRENCH HUMANITIES OF THE 1940s–1960s - Холодинська, Світлана (Ukrainian Cultural Studies, 2023)
In the second half of the 20th century, discussions around the understanding of crisis phenomena that permeated all spheres of human life became more frequent, in particular, the spheres of art and aesthetics were also touched upon. The crisis in the artistic sphere was connected with the general cultural crisis of the late 19th and early 20th centuries, the decline of spirituality, and the relativization of values, primarily moral and aesthetic. Analysis of the crisis in the sphere of artistic practice and aesthetics of the 20th century was the subject of scientific research by several representatives of Polish aesthetics of the second half of the 20th century: R. Ingarden, S. Morawski, B. Dziemidok, and others. The primary attention of these thinkers was devoted to the understanding of transformational processes in modern artistic creativity and the analysis of its influence on aesthetics with a clear emphasis on the importance of the axiological perspective. A thorough analysis of the problems of the crisis in artistic creativity and aesthetics of the 20th century can be found in the works of S. Morawski. He studied the causes and consequences of transformations in artistic creativity since the beginning of the 20th century, in particular, the consequences for the formation of the modern axiosphere, and its role in changing modern aesthetic consciousness. However, S. Morawski’s prediction regarding the replacement of aesthetics with anti-aesthetics was not confirmed. On the contrary, art that implements aesthetic values has survived, although the range of aesthetic values has increased significantly. Modern philosophy of art is open to the most controversial artistic proposals. This is because it breaks with those normative principles that limit freedom. The most important thing, however, is that normative and descriptive aesthetics always have an axiological character, which all representatives of Polish aesthetics emphasized in the second half of the 20th century.